A study on the relationship between organizational learning and organizational commitment at Niaga Global, Cheras, Selangor / Muhammad Haziq Mohammad Ali - Mohammad Ali, Muhammad Haziq (Faculty of Business and Management, 2019)
This research discussed on the relationship between Organizational Learning and Organizational Commitment at Niaga Global. The study aims to investigate the relationship between organizational learning which is motivation, leadership, innovation and teamwork with organizational commitment among staff at Niaga Global Cheras, Selangor. Based on the previous researches, lack of organizational learning can give an effect for the organizational commitment. According to Hatane, S. E. (2015), when the application of learning organization is use in the organization, it will lead to increase employee ability and to adopt the changes of innovation in the organization. For the methodology, due to the number of population at Niaga Global, there is no sampling techniques apply for this study. All the employees were chosen to be the respondent for this study. From the finding on this research, the highest factor of organizational learning at Niaga Global is teamwork (22.9500). Meanwhile for the relationship there is strong and positive relationship between two variables. The highest relationship between two variables is innovation and organizational commitment with value r (=.906). In a conclusion, these studies have accomplished the objectives that investigating this research.